Effect of UV-C irradiation on post harvest quality of oyster mushrooms - Desmukh, Shikha; K, Ranjitha; Pandey, Meera (Mushroom Research, 2015)
Effect of ultraviolet (UV-C ) treatment on shelf life, ferric reducing antioxidant capacity, phenols, radical scavenging activity and microbiological quality of oyster mushrooms (Pleurotus florida and Pleurotus sajor-caju) stored at ambient temperature (25-27Â°C) was studied. UV irradiation did not improve shelf life of oyster mushrooms. Irradiation dose >1.34 and 3.35 kJ (2 and 5 minutes) resulted in deterioration of marketability of P. florida and P. sajor-caju during 24 hrs storage.Â  After 24 hrs of storage, highest antioxidant capacity was shown in P. florida irradiated with UV rays for 1 minute (0.67 kJ) and P. sajor-caju for 5 minutes (3.35kJ). UV-C irradiation for 5 minutes also caused an increased phenolics accumulation in both Pleurotus spp, without changing radical scavenging activity significantly. Mesophilic bacterial count also reduced till 3 and 5 minutes of irradiation in P florida and P. sajor-caju.